2014 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining (ASONAM 2014) 2014
DOI: 10.1109/asonam.2014.6921683
|View full text |Cite
|
Sign up to set email alerts
|

A study of age and gender seen through mobile phone usage patterns in Mexico

Abstract: Mobile phone usage provides a wealth of information, which can be used to better understand the demographic structure of a population. In this paper we focus on the population of Mexican mobile phone users. Our first contribution is an observational study of mobile phone usage according to gender and age groups. We were able to detect significant differences in phone usage among different subgroups of the population. Our second contribution is to provide a novel methodology to predict demographic features (nam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 11 publications
0
47
0
Order By: Relevance
“…Although optimal s jk values are quite independent of β, the performances are not, with highest accuracy gains in the range [70,85]%. This range covers the accuracies reached by stateof-the-art techniques aiming to predict gender using individuallevel features [4], [5], [26]. Likewise, for an assortativity coefficient similar to the one of G S (≈ 0.25), the accuracy gains on synthetic networks are significant when β ∈ [0.62, 0.92].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although optimal s jk values are quite independent of β, the performances are not, with highest accuracy gains in the range [70,85]%. This range covers the accuracies reached by stateof-the-art techniques aiming to predict gender using individuallevel features [4], [5], [26]. Likewise, for an assortativity coefficient similar to the one of G S (≈ 0.25), the accuracy gains on synthetic networks are significant when β ∈ [0.62, 0.92].…”
Section: Resultsmentioning
confidence: 99%
“…Our methodology is now tested on G S , while simulating individual prior predictions. The obtained performances are compared with the results of a baseline method, termed the reaction-diffusion algorithm [5].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Homophily is used to describe peoples' tendency to associate with those that are similar to them [22]. Studies have shown that there is significant difference in the phone usage of different genders and age groups, and the usage patterns can be used to predict the demographic features [23], [24]. Additionally, homophily can be used to predict similarities between people who interact frequently or to predict interactions between people who behave in a similar way [13], [25].…”
Section: Related Workmentioning
confidence: 99%